3D printing of glass fiber reinforced acrylonitrile butadiene styrene and investigation of tensile, flexural, warpage and roughness properties. Issue 9 (4th August 2022) - Amiri, Aria; Zolfaghari, Abbas; Shakeri, Mohsen
Abstract: Three‐dimensional (3D) printing or additive manufacturing (AM) enables to fabricate, complex parts in low quantities without expensive molds or tools in short time. While several 3D printing methods are available, printing with the method of fused deposition modeling (FDM) is particularly widespread because of the simplicity and potential applicability. The applications of FDM to obtain strong components used in aerospace and automotive industries are widely being explored. This study investigates mechanical properties of 3D printed parts with composite filaments made by acrylonitrile butadiene styrene (ABS)/short glass fibers (SGFs). At first, composite filaments with varying GF contents 5, 10, and 15 wt% were manufactured. In addition, maleic anhydride grafted ABS (ABS‐g‐MA) as coupling agent, nozzle temperature and raster angle orientation were considered as other parameters. Results showed that with 15 wt% of GF, means of tensile and flexural strengths were increased 33% and 36%, respectively. Meanwhile, tensile and flexural moduli were improved 57% and 62%. Among the different raster angle, 0° had the best mechanical properties. Maximum ultimate tensile strength was obtained 61 MPa. Warpage and surface roughness were measured in this study. Generally, nozzle temperature and coupling agent did not have any significant effects on all the results in this study. Abstract :